On the supramolecular outcomes of fluorination of cyclohexane-5-spirohydantoin derivatives. Issue 13 (17th March 2021) - Gak Simić, Kristina; Đorđević, Ivana; Lazić, Anita; Radovanović, Lidija; Petković-Benazzouz, Marija; Rogan, Jelena; Trišović, Nemanja; Janjić, Goran
Abstract : The crystal packing of two spirohydantoins was analyzed through the contribution of dimeric motifs and different interactions. The cooperative effect was rationalized in terms of the formation of a new region, as a result of the F⋯F interaction. Abstract : The quantitative assessment of intermolecular interactions and their cooperative effects has been performed in spirohydantoin-based model compounds, 3-benzoyl-1, 3-diazaspiro[4.5]decane-2, 4-dione (1 ) and 3-(4-fluorobenzoyl)-1, 3-diazaspiro[4.5]decane-2, 4-dione (2 ), through single crystal X-ray crystallography and quantum chemical studies. In both crystal structures, molecules generate the same hydrogen-bonded centrosymmetric R22(8) synthon. The extended supramolecular architectures depend on the C–H⋯O, C–H⋯π, stacking interactions and parallel interactions at large offsets, which lead to molecular sheets and further, with the assistance of the C–H⋯F interaction in the case of 2, to three-dimensional networks. Electrostatic potential maps have indicated that formation of the intermolecular F⋯F interaction in the crystal structure of 2 results in a new region with a larger surface area and a higher negative potential in comparison to the individual fluorine atoms. Establishment of this interaction leads to strengthening of the interaction of one of the fluorine atoms with a third molecule from the environment which does not interact with both of them. When this third molecule interacts with both fluorine atoms simultaneously, the calculations have shown that the effect of strengthening of the individual interactions due to formation of the F⋯F interaction is absent.